IMPLEMENTATION OF CHARACTER EDUCATION VALUES IN ISLAMIC SCHOOL INTEGRATED TO IBNU ABBAS KEBUMEN - Indri Novianti; Lutfiana Rahmayanti; Rizki Isnaeni Putri; Siti Fatimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to: a) find out the method of implementing the values of selected character education such as religious, honest, diligent, disciplined, and caring / responsible; b) knowing the religious behavior, honesty, diligence, discipline, and caring / responsibility of students in SDIT Ibn Abbas; and c) knowing the barriers to the application of character education values and solutions sought by the teacher. Research is a qualitative descriptive study by collecting data through interviews and questionnaires. The results of observation showed that the religious aspect was 54.73% with the category "enough", honest aspects 62.55% with the category "enough", aspects of diligence 82.30% with the category "good", disciplinary aspects 82.71% with the category "good" and environmental aspects of 63.73% with the category "enough". The obstacle experienced by the teacher is when the planting taught by the teacher is not in harmony with the one at home. So that the solution sought by the teacher is to communicate more deeply with students and parents of students / guardians of students.